Levodopa-benserazide Interaction with Enteral Nutrition: A Case Report - Foroud Shahbazi; Hasanali Karimpour; Elham Hosseini (Research Center for Rational Use of Drugs (RCRUD), 2018)
Levodopa is considered one of the most important medication for parkinson symptoms control, it also first line agent for elderly and patients who symptoms don't control with other agents. However, it has several drug and nutrition interactions. A few case of levodopa enteral nutrition has been reported.